The effect of coagulation factors in 2019 novel coronavirus patients: A systematic review and meta-analysis. Issue 7 (19th February 2021) - Xiang, Guiling; Hao, Shengyu; Fu, Cuiping; Hu, Weiping; Xie, Liang; Wu, Qinhan; Li, Shanqun; Liu, Xuhui
Abstract: Background: The role of coagulation dysfunction in Severe Coronavirus Disease 2019 (COVID-19) is inconsistent. We aimed to explore the impact of coagulation dysfunction amongst patients with COVID-19. Methods: We searched PubMed, Cochrane and Embase databases from December 1, 2019 to April 27, 2020 following Meta-analysis of Observational Studies in Epidemiology (MOOSE) guidelines. Data about coagulation (Platelets, PT, APTT, fibrin, fibrinogen degradation products, D-dimer), prevalence of coagulation dysfunction and mortality were extracted. Meta regression was used to explore the heterogeneity. Results: Sixteen observational studies were included, comprising 2, 139 patients with confirmed COVID-19. More severe COVID-19 cases tended to have higher mean D-dimer (SMD 0.78, 95% CI 0.53 to 1.03, P  < .001). The similar pattern occurred with PT and fibrin, with a contrary trend for PLTs. Coagulation dysfunction was more frequent in severe cases compared to less severe (SMD 0.46, 95% CI 0.25 to 0.67, P  < .001). Higher mortality was associated with COVID-19-related coagulopathy (RR 10.86, 2.86 to 41.24, P  < .001). Prevalence of ARDS was increased in more severe patients than less severe cases (RR 16.52, 11.27 to 24.22, P  < .001). PT, fibrin and D-dimer levels elevated significantly in non-survivors during hospitalization. Conclusion: Presence of coagulation dysfunction might be associated with COVID-19 severity, and coagulopathy might be associated with mortality. Coagulation markers including PT, fibrin and D-dimer may imply the progression of COVID-19. This illuminates the necessity of effectively monitoring coagulation function for preventing COVID-19-related coagulopathy, especially in severe patients. For the obvious heterogeneity, the quality of the evidence is compromised. Future rigorous randomized controlled trials that assess the correlation between coagulation and COVID-19 are needed. Trial registration: PROSPERO (CRD42020183514). Abstract : Supplemental Digital Content is available in the text